Cultural Literacy Based Critical Reading Teaching Material with Active Readerstrategy for Junior High School - Vismaia S Damaianti; Lira Fessia Damaianti; Yeti Mulyati (International Journal of Evaluation and Research in Education (IJERE), 2017)
This article describes the findings of a study aimed at producing a set of cultural literacy-oriented critical reading teaching material. This material is developed as a countermeasure to the increasingly thin sensitivity of society, especially the students toward noble values of religion, custom, and culture. With this material student get a significant critical understanding of the discourse with the content of noble value of Indonesian culture. The understanding is attained by students through active reader strategy. There are four important principles developed in understanding the text through this strategy, namely 1) building basic understanding of the text, 2) conducting reading activities in chronological order of the text, 3) identifying the style and language of the text, and 4) critically deepening the understanding of the text. The emphasis on cultural critical understanding became the focus of this research. Thus, critical reading question technique 501 is required. With this technique student can predict causation, establish logical and emotive understanding, and predict the implications of ideas. The implementation of development of this teaching material is based on the stages of Design Based Research. Data is obtained through expert scales and trials to junior high school students in Bandung. The result of this research is a critical reading textbook based on cultural literacy with active reader strategy that is effective to be used for junior high school students. The implication of this research is the acquisition of students' sensitivity toward noble values of religion, custom, and culture that can be internalized in their lives.